Akibat Hukum Terhadap Anak Hasil Perkawinan Siri Pasca Putusan Mahkamah Konstitusi (Lex Jurnalica, 2014)
AbstractDefinition of marriage siri not expressly provided in the Civil Code and the Law 1 of 1974 on Marriage . Article 2 of Law No. 1 of 1974 on Marriage just describe the sense of legal marriage. Therefore, legally , marriage series certainly has a position and due to the status and position of a child . The issue of how the legal position of unregistered marriages views of Law 1 of 1974 concerning marriage and how the legal effect of the position of children unregistered marriages are reviewed according to Law No. 1 of 1974 on Marriage after the verdict of the Constitutional Court No. 46 / PUU - VIII / 2010? (Case Study: Determination No. 683 / Pdt.P.2011.PA.SBY). The method used is a normative legal research, descriptive research analisitis properties, as well as qualitative data analysis. The results show, that the legal position of unregistered marriages is actually the same as a legal marriage as specified in Article 2 paragraph (1) of Law No. 1 of 1974 on Marriage. However, due to not do the recording of the administration of the wedding series as provided in Article 2 paragraph (2) of Law No. 1 In 1974, the legal position of unregistered marriages , can not be recognized. Second , that the legal consequence of the position of children unregistered marriages when viewed according to Law No. 1 of 1974 on Marriage of which is to make the status and position of a child is not recognized when the child was born before the marriage of his parents registered and legally recognized and recording his own birth made one (1) year after the child is born that has exceeded the time limit of birth registration as defined in Article 27 of Law No. 23 Year 2006 concerning Population Administration. Therefore, in taking notes of his birth , requires the court to make a determination of the child can be recognized status and position so that it becomes the same as the legitimate child as defined in Article 32 paragraph (2) of Law No. 23 Year 2006 concerning Population Administration, which reads: